Blending QR code with video learning in the pedagogical process for the college foundation level. Issue 1 (11th December 2019) - Ahmed, Waleed; Zaneldin, Essam
Abstract : Purpose: This paper aims to use quick response (QR) code along with online videos to teach one of the college foundation courses in an international institution to enhance the grasp of the students and to boost the students' learning outcomes. Design/methodology/approach: The study discussed and elaborated the findings that mainly focused on the usage of the online resources to teach Engineering Economy course. Besides, the authors analyzed how the gender may have different feedback for the student. Findings: The study emphasized on the expectations of the students to use videos in the learning experience that preferred to be developed by course educator and to be published on the university platform, like blackboard or faculty website, that conforms university transformation vision undergoing nowadays. It is recommended to have a successful learning experience; it is the educator's responsibility to improve the personal digitization skills that would be used in the e-learning implementations, that will be used for the educational technology, which requires the use of creative media production mobile applications. Practical implications: The education field has witnessed significant development over the past years in terms of using digital technologies as pedagogical tools to enhance the students' learning experience especially the internet, where the traditional trends become outdated to be used in the classrooms. One of the main players in this field is videos that are considered as the main influencer to this educational change, where it has been demonstrated to and boost the quality of the learning experience. Originality/value: In this study, students participated to explore the usefulness of using online learning through using videos blended with QR code to enhance the students' performance in understanding one of the undergraduate foundation courses in the college of engineering, namely, engineering economy. A survey was distributed to students after the core material of the course was covered. The collected responses were then studied and analyzed.